What Experts Say About Teachers' Understanding Of Technological Innovation In Their Work (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This qualitative study measured experts' understanding and expressions about teachers' understanding of technological innovations in Indonesia's teaching assignments. Success in carrying out teaching assignments for school students closely related to technological innovation skills in management in today's digital time. To facilitate the discussion of study topics, we have collected secondary data from many scientific reports and studies, including scientific reports, literature reviews, and direct observations to several schools about how teachers have innovated technology in helping their teaching assignments in the global era. After the data, we then analyzed it with the in-depth interpretation, which consisted of the coding process, before concluding. In concluding, we pay attention to the validity and reliability aspects of the data findings so that our answers have answered this educational study's questions. Our data search process used data search engines such as Google Search and Google scholar with the help of keywords, "Understanding Teacher," Technology Innovation, "TeacherTeacher Working, "What experts Say on teachers Understanding on technology, "etc. Finally, we can report that teachers' understanding in Indonesia still considers that technology such as smartphones, laptops, and the like are still limited as consumptive users, not yet productive like the capacity of technology for teachers and other professionals' duties jobs. Therefore, this finding is a good insight for teacher teachers, researchers, and policy-making in education and training.